The Reconstructing the Teleological Foundations of Islamic Education: A Thematic Educational Interpretation Addressing the Fragmentation of Spiritual and Educational Aims - Zahra Uswah Hasanah; Kresna Ralfsanjani; Khoerunnisa; Hilman Abdul Aziz; Hafid Muslih; Cecep Anwar (Jurnal al-Thullab, 2025)
Contemporary Islamic education faces a fragmentation of objectives between spiritual and pedagogical-instrumental orientations. Education tends to emphasize technical competence and market needs, while transcendental and Qur'anic values ​​are marginalized. This article aims to reconstruct the teleology of Islamic educational objectives based on thematic interpretations of the Qur'an. The study uses a qualitative approach with library research. Primary data consists of Qur'anic verses on educational objectives, while secondary data include tafsir books, Ta'lim al-Muta'allim by az-Zarnuji, and contemporary Islamic educational literature. Analysis was conducted using the maudhu'i tafsir method of al-Farmawi and content analysis. The results show that the objectives of Islamic education are integrative, encompassing spiritual, moral, intellectual, social, and ubudiyah dimensions, making them relevant to addressing the challenges of contemporary education.